Cherry Phenological Phases Flowering and Ripping Periods - Azamovna , Kimsanova Kholida; Khusanboy’s , Tursunboyeva Mastura (Miasto Przyszłości, 2024)
Creating a garden, creating fruit varieties with high productivity and resistance to various diseases and pests is one of the urgent tasks facing fruit growers today. We are carrying out scientific research in order to create orchards based on intensive technology by selecting suitable clone grafts for cherry fruit.